QUALITY ASSESSMENT OF TEACHING THE COURSE "THE BASICS OF STATE AND LAW" IN TERMS OF STUDENTS' OPINIONS FROM THE FACULTIES WITH SPORTING PROFILE - Ina Pârlii (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The assessment of the teaching quality implies a process that allows the appreciation of the effectiveness of academic staff which ensures a specific component from a specific study program. Assessment practices raises questions on what counts as a "science / to know" or "knowing / knowledge" in a certain culture. By the skill to utilize resources and management capacity of the educational process (therefore, the teaching strategy) depend, ultimately, the academic obtained performances by the students. Thus, to establish an evaluation strategy in education is equal to fixing when assessing, in what form, by what methods and means, how you value the information obtained etc. Of course, in the end, according to the conclusions, the student will change its strategy of learning, the teacher the one of teaching and manager the managerial strategy. The assessment strategy shows how to integrate the action of assessment (achievable by the measuring-appraisal-decision operations) in the structure of didactic teaching activity functioning. The evaluation strategy reflects the increasing trend of evaluative actions: from the traditional checks to assess processes and progress conditions of teaching activities, situations of training / learning.